2012
DOI: 10.2147/ijn.s24083
|View full text |Cite
|
Sign up to set email alerts
|

Development of an MRI-visible nonviral vector for siRNA delivery targeting gastric cancer

Abstract: An antibody-directed nonviral vector, polyethylene glycol-grafted polyethylenimine functionalized with superparamagnetic iron oxide nanoparticles and a gastric cancer-associated CD44v6 single-chain variable fragment (scFv CD44v6 ,-PEG-g-PEI-SPION), was constructed as a gastric cancer-targeting and magnetic resonance imaging (MRI)-visible nanocarrier for small interfering RNA (siRNA) delivery. Biophysical characterization of PEG-g-PEI-SPION and scFv CD44v6 -PEG-g-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, PEI can be easily modified by coupling some small molecules to endow it specific targeting ability. PEI can also induce cytotoxicity at high molecular weight and in high concentration, which is usually not the case in its application as a nanoparticle carrier 8 .…”
mentioning
confidence: 99%
“…In addition, PEI can be easily modified by coupling some small molecules to endow it specific targeting ability. PEI can also induce cytotoxicity at high molecular weight and in high concentration, which is usually not the case in its application as a nanoparticle carrier 8 .…”
mentioning
confidence: 99%
“…As previously reported, most obvious MRI contrast could be achieved at the injection dose of 4.48 µg Fe/g body weight [20]. Therefore, an injection dose of 4.48 µg Fe/g body weight was used to detect tumors by MRI in our study.…”
Section: Methodsmentioning
confidence: 78%
“…29 Some studies showed that using PEI-coated SPIONs for transfection leads to less toxicity and improved efficiencies compared to the use of only PEI. 30,31 Moreover, Lipofectamine is another reagent also widely used for transfection of cells with a very similar experimental protocol of PEI. However, the main difference between Lipofectamine and PEI is their mechanism of action on the cell membrane.…”
Section: Results and Discussionmentioning
confidence: 99%
“…33 Although some studies use Lipofectamine as a control, in most of the PEI-mediated magnetofection studies, free PEI is used as a common control of its nanoformulated versions. 30,31,3436 Accordingly, in our experimental setup, we investigate the effect of magnetofection by applying a cationic polymer-based transfection procedure using PEI-coated SPIONs. Therefore, we use free PEI rather than lipofectamine.…”
Section: Results and Discussionmentioning
confidence: 99%